BUILDING A CULTURE OF CREATIVE THINKING IN BUSINESS STUDIES - Mačerauskienė, Nida (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Creativity is considered as an intangible characteristic that drives business to success. Creative persons play an important role in fostering both technical and social innovation and progress. Contemporary higher education graduates are expected to possess soft skills including creative thinking, problem-solving, critical thinking, flexibility, motivation, positivity and others. Therefore, the research was designed with the aim to enhance the understanding of the concepts of creativity and creative thinking and to address the question of how creativity and the process which we use when we come up with a new idea can be enhanced within and by higher education institutions. This study examines a creativity-driven study environment to promote a safe, non-judgmental atmosphere and the Creative Platform process meant to develop creativity during regular practical tasks to make it an involuntary reflex and to discover new viewpoints, perspectives, and solutions to any business problem. The framework of the research is based on the analysis of literature and experimental research methods. The results revealed that using special techniques, purposeful creative thinking can be developed beyond creativity subject. Moreover, interdisciplinarity teams lead to better solutions.